Congenital diaphragmatic hernia in pediatric patients: Open versus thoracoscopic repair: A systematic review and meta-analysis - Fabiola Cassaro; Salvatore Arena; Angela Alibrandi; Roberta Bonfiglio; Pietro Impellizzeri; Carmelo Romeo (International Journal of Abdominal Wall and Hernia Surgery)
PURPOSE: Repair of congenital diaphragmatic hernia (CDH) includes both mini-invasive and open approaches. We aimed to conduct a comprehensive meta-analysis comparing the outcomes of thoracoscopic and open CDH repairs in the pediatric population. MATERIALS AND METHODS: A literature review using as keywords “thoracoscopy,” “open surgery,” and “CDH” was performed. The primary endpoints of the study were to evaluate mortality as well as major intraoperative and postoperative complications, including CDH recurrence. Secondary endpoints were the use of a patch, the length of stay, and operative time. RESULTS: On 88 papers, 20 met the inclusion criteria (902 patients: 458 treated thoracoscopically and 444 undergone open surgery). There was no significant difference in major postoperative complications (P = 0.695) or use of patch (P = 0.282). Conversely, the thoracoscopic approach significantly reduces mortality (P = 0.001) and length of stay (P < 0.001). Open surgery reduces the incidence of major intraoperative complications (P < 0.001), recurrences (P = 0.025), and operative time (P < 0.001). CONCLUSION: According to our analysis, open surgery seems to reduce intraoperative complications and recurrences. Moreover, thoracoscopy seems to show an improvement in mortality and length of stay. However, the lack of randomization in all the analyzed studies could represent a potential bias in the final conclusion and need a careful evaluation.